2007
DOI: 10.1016/j.tics.2007.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The ‘when’ pathway of the right parietal lobe

Abstract: The order of events, whether two events are seen as simultaneous or successive, sets the stage for the moment-to-moment interpretation of the visual world. Evidence from patients who have lesions to the parietal lobes and transcranial magnetic stimulation studies in normal subjects suggest that the right inferior parietal lobe underlies this analysis of event timing. Judgment of temporal order, simultaneity and high-level motion are all compromised following right parietal lesions and degraded after transcrani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
151
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(172 citation statements)
references
References 55 publications
17
151
2
2
Order By: Relevance
“…Recent studies indicate separate processing of 'when' and 'what' in the human brain (Nishida & Johnston 2002;Battelli et al 2007Battelli et al , 2008). Both the synchrony task and binding task are judgements of relative temporal phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicate separate processing of 'when' and 'what' in the human brain (Nishida & Johnston 2002;Battelli et al 2007Battelli et al , 2008). Both the synchrony task and binding task are judgements of relative temporal phase.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially relevant loci include the parietal cortex, which has connections with multiple sensory areas (Lewis & Van Essen 2000) and plays a critical role in spatial cross-attribute binding (Friedman-Hill et al 1995;Robertson 2003). Particularly of interest is the right inferior parietal lobe (IPL), which has been suggested to be a cortical area responsible for 'when' processing (Battelli et al 2001(Battelli et al , 2007(Battelli et al , 2008. It has been reported, for instance, that damage to this area impairs synchrony judgement between spatially separated flickers (similar to the current V lum 2V lum condition; Battelli et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Humans tend to naturally attribute causal relationships and intentionality to moving geometric figures (Michotte 1954); perceptual causality may derive from specialized automatic rules (Scholl & Tremoulet 2000), but it remains unclear whether these rules underlie perceptual processing or entail higher cognitive processes. One functional magnetic resonance imaging (fMRI) study showed activation of the right inferior prefrontal cortex during observation of stimuli leading to perceptual causality (Fugelsang et al 2005); this area is crucially activated in time perception (Lewis & Miall 2006) and in the retrieval of temporally structured sequences (Fuster 2001), suggesting the implication of central mechanisms for the evaluation of temporal order (Pöppel 1997)-see also Battelli et al (2007) for a review on the involvement of parietal cortex in ordering events.…”
Section: An Amodal Representational Space For Time Perception?mentioning
confidence: 99%
“…when participants attend to time. With respect to the hypothesis that time representations acquire a degree of abstraction only when they reach the global workspace, evidence is accumulating for shared neural substrates underlying the computations of time, space and numerosity as magnitudes (Walsh 2003;Bueti & Walsh 2009): repetitive transcranial magnetic stimulation (rTMS) over the parietal cortex, also implicated in the representation of numbers (Hubbard et al 2005), impairs temporal perception (Giacomo et al 2003;Walsh 2003;Alexander et al 2005;Battelli et al 2007;Koch et al 2009). Recent psychophysical data have demonstrated the automatic influence of size (Xuan et al 2007) and numerosity (Dormal et al 2006) on duration judgements; however, and importantly, duration does not impair numerosity (Dormal et al 2006).…”
Section: Shuffling Time In the Brainmentioning
confidence: 99%
“…Temporal perception also depends on low-level temporal visual acuity (e.g. Kelly 1979) as well as temporal attention, which also has limited resolution (Battelli et al 2007). For example, humans can typically detect individual events at almost 60Hz, just slower than flicker of fluorescent lighting, but cannot do so at temporal frequencies above about 7Hz (e.g.…”
mentioning
confidence: 99%